The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3748/wjg.v27.i31.5247
|View full text |Cite
|
Sign up to set email alerts
|

Tailored eradication strategy vs concomitant therapy for Helicobacter pylori eradication treatment in Korean patients

Abstract: BACKGROUND Antibiotic resistance to Helicobacter pylori (H. pylori ) infection, which ultimately results in eradication failure, has been an emerging issue in the clinical field. Recently, to overcome this problem, an antibiotic sensitivity-based tailored therapy (TT) for H. pylori infection has received attention. AIM To investigate the efficacy and safety profiles of TT for H. pylori infe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 54 publications
(67 reference statements)
1
11
0
Order By: Relevance
“…After removing duplicates, a total of 13,941 citations were screened. After reviewing the abstracts and full texts, 47 studies (Romano et al, 2000 , 2003 ; Toracchio et al, 2000 ; Avidan et al, 2001 ; Street et al, 2001 ; Lamouliatte et al, 2003 ; Miwa et al, 2003 ; Neri et al, 2003 ; Marzio et al, 2006 ; Yahav et al, 2006 ; Furuta et al, 2007 ; Kawai et al, 2008 ; Wang et al, 2008 ; Zhou et al, 2010 , 2016 ; Bontems et al, 2011 ; Molina-Infante et al, 2012 ; Cosme et al, 2013 , 2016 ; Lee et al, 2013 ; Martos et al, 2014 ; Park et al, 2014 ; Dong et al, 2015 ; Zhuo et al, 2015 ; Kwon et al, 2016 ; Miyaki et al, 2016 ; Ferenc et al, 2017 ; Gweon et al, 2018 ; Huang et al, 2018 ; Liou et al, 2018 ; Mascellino et al, 2018 ; Tanabe et al, 2018 ; Byambajav et al, 2019 ; Chen et al, 2019 ; Cho et al, 2019 ; Choi et al, 2019 , 2021 ; Delchier et al, 2019 ; Ong et al, 2019 ; Pan et al, 2020 ; Saracino et al, 2020 ; Zhang et al, 2020 ; Bonoso Criado et al, 2021 ; Cha et al, 2021 ; Chang et al, 2021 ; Choe et al, 2021 ) were finally included in the present systematic review. A total of 54 different treatment comparisons were evaluated both in the quantitative and qualitative synthesis since some studies assessed more than one treatment comparison.…”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates, a total of 13,941 citations were screened. After reviewing the abstracts and full texts, 47 studies (Romano et al, 2000 , 2003 ; Toracchio et al, 2000 ; Avidan et al, 2001 ; Street et al, 2001 ; Lamouliatte et al, 2003 ; Miwa et al, 2003 ; Neri et al, 2003 ; Marzio et al, 2006 ; Yahav et al, 2006 ; Furuta et al, 2007 ; Kawai et al, 2008 ; Wang et al, 2008 ; Zhou et al, 2010 , 2016 ; Bontems et al, 2011 ; Molina-Infante et al, 2012 ; Cosme et al, 2013 , 2016 ; Lee et al, 2013 ; Martos et al, 2014 ; Park et al, 2014 ; Dong et al, 2015 ; Zhuo et al, 2015 ; Kwon et al, 2016 ; Miyaki et al, 2016 ; Ferenc et al, 2017 ; Gweon et al, 2018 ; Huang et al, 2018 ; Liou et al, 2018 ; Mascellino et al, 2018 ; Tanabe et al, 2018 ; Byambajav et al, 2019 ; Chen et al, 2019 ; Cho et al, 2019 ; Choi et al, 2019 , 2021 ; Delchier et al, 2019 ; Ong et al, 2019 ; Pan et al, 2020 ; Saracino et al, 2020 ; Zhang et al, 2020 ; Bonoso Criado et al, 2021 ; Cha et al, 2021 ; Chang et al, 2021 ; Choe et al, 2021 ) were finally included in the present systematic review. A total of 54 different treatment comparisons were evaluated both in the quantitative and qualitative synthesis since some studies assessed more than one treatment comparison.…”
Section: Resultsmentioning
confidence: 99%
“…A flow chart explaining the study selection is shown in Figure 1. Of the 2156 titles initially found by the literature searches, 34 studies were found suitable for meta‐analysis 28–61 . Two studies 50,61 had 3 arms comparing the tailored treatment regimen with two different empiric regimens.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, these two studies contained 2 sets of data each, making the total number of pair comparisons in the meta‐analysis 36. There were 25 randomized control trials (RCTs) 28,29,31,35,37,38,40–45,49–57,59,61 and 9 non‐randomized trials (NRT) 30,32–34,36,39,46,58,60 . Thirty‐two of the enrolled studies 29–57,59–61 contained adult population, and 2 studies 28,58 contained children.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table A1 shows the randomized clinical trials published in the last 10 years, comparing tailored and empirical therapies in first-line eradication treatment [12,[43][44][45][46][47][48][49][50][51]. Although tailored therapy is widely considered as superior to empirical therapy in first-line treatment, the overall results are diverse, in which some studies showed no difference at all between the two therapy groups.…”
Section: Tailored Therapymentioning
confidence: 99%